Analisis Pendapatan dan Nilai Tambah Industri Rumah Tangga Kelapa Gongseng (U Neulheu) Kecamatan Jangka Kabupaten Bireuen Provinsi Aceh - M. Saleh; M Rasyidin; Hakim Muttaqim (ARBITRASE: Journal of Economics and Accounting, 2022)
Jangka District, Bireuen Regency, Aceh Province is a home industry area that processes coconuts into a processed product in the form of gongseng coconut (Uneulheu), a special Acehnese cooking spice. The purpose of this study was to determine the amount of income received and to know the amount of value added from the Uneulheu processing business in the home industry of Jangka District, Bireuen Regency, Aceh Province. Research method Case study analysis of income and analysis of added value and the number of respondents as many as 17 household industries. The results showed that the business of processing coconut gongseng in the home industry is profitable. Apart from gongseng coconut, the household industry also obtains additional income from coconut derivative products such as copra and shells. Furthermore, the added value obtained by the home industry in producing gongseng coconut is 9.47% percent. With an added value of Rp. 5,063 per Kg per production.